2022
DOI: 10.3390/ijerph19159151
|View full text |Cite
|
Sign up to set email alerts
|

What Levers to Promote Teachers’ Wellbeing during the COVID-19 Pandemic and Beyond: Lessons Learned from a 2021 Online Study in Six Countries

Abstract: To highlight effective levers to promote teachers’ wellbeing worldwide, particularly during difficult times such as the COVID-19 pandemic, we investigated work-related factors associated with teacher wellbeing, across borders and cultures. In six countries/territories, we examined the factors that were most consistently and strongly associated with two indicators of wellbeing at work: (i) job satisfaction; and (ii) work/life balance, and three indicators of general wellbeing: (i) subjective health; (ii) mental… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 71 publications
0
10
0
1
Order By: Relevance
“…Finally, our results are based on French pre-pandemic data and generalizability is not a matter of course. Given the heterogeneity in teachers’ sociodemographic and cultural backgrounds across countries [ 58 , 59 ], cross-cultural studies are needed to expand the view on teacher health around the world. Furthermore, the present analysis applies to a time before the COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, our results are based on French pre-pandemic data and generalizability is not a matter of course. Given the heterogeneity in teachers’ sociodemographic and cultural backgrounds across countries [ 58 , 59 ], cross-cultural studies are needed to expand the view on teacher health around the world. Furthermore, the present analysis applies to a time before the COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…Be to, mokytojai pabrėžia pasitikėjimo mokyklos vadovu reikšmę ir teigia, kad tai didina saugumą dėl darbo (Hendriks et al, 2020). Tyrėjai pastebi, kad kuo komunikacija mokykloje geresnė, tuo mokytojų pasitenkinimas darbu yra didesnis (Billaudeau et al, 2022), o nesaugumas dėl darbo -mažesnis (Saeed et al, 2021). Komunikacijos organizacijoje kokybė prognozuoja mokytojų pasitenkinimą darbu, o šis siejasi su mokytojų įsipareigojimu organizacijai (De Nobile, 2017).…”
Section: Mokyklos Kaip Organizacijos Funkcionavimo Mokytojų Profesinė...unclassified
“…Further, recent literature reviews on well‐being indicated that the majority of the discussions centered around work‐related individual and contextual factors, particularly the need for social relationships and a positive work atmosphere (Billaudeau et al, 2022; Hascher & Waber, 2021). However, the drastic transition in the way teaching occurred during the COVID‐19 pandemic indicated that several additional significant factors stemming from the challenges of teaching online and working remotely from home (L. E. Robinson et al, 2022) were significant contributors to high stress and lower well‐being.…”
Section: Introductionmentioning
confidence: 99%